Factors Affecting Symptoms of Depression and Anxiety among Pregnant Women during COVID-19 Pandemic - Aqilah Syahrina Syauki; Hartati; Raissa Nurwany; Syarifah Aini (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2024)
Background: Changes in social life have a negative impact on mental health, leading to conditions such as depression and anxiety. Pregnant women are particularly vulnerable to mental health disorders, including depression and anxiety. This study aims to identify factors that influence symptoms of depression and anxiety in pregnant women during the COVID-19 pandemic. Methods: Analytic observational research was used in this study. Primary data were collected from November 1 to November 28, 2021. The data collected came from distributing paper questionnaires and online questionnaires at 7 Independent Midwifery Clinics. The measurement instruments used include Beck Anxiety Inventory (BAI), Fear of COVID-19 Scale (FCV-19S), and Beck Depression Inventory (BDI). Results: The results showed that out of 308 pregnant women in Palembang, 13.0% experienced mild depression symptoms, 5.2% experienced moderate depression symptoms, and 1.6% experienced severe depression symptoms. In addition, 41.9% of participants reported anxiety symptoms, which were categorized as mild to moderate anxiety (31.5%), moderate to severe anxiety (9.1%), and severe anxiety (1.3%). There was a significant association found in the bivariate analysis between depressive symptoms and the age maternal women, a significant association of anxiety and depression with abortion history, and a significant association of depressive symptoms and anxiety symptoms with fear related to COVID-19. Conclusions: Research reveals multiple relationships between maternal age and depressive symptoms; between an abortion history and anxiety symptoms; between fear of COVID-19 and the symptoms of depression and anxiety. Counselling in mental health is necessary, especially for pregnant women with high-risk of depression and anxiety.